Natural stress vs. anthropogenic pressure. How do they affect benthic communities?. (August 2022) - Puente, A.; Gómez, A.G.; de los Ríos, A.; Galván, C.
Abstract: This study compares the role of salinity regime and chemical pollution in the biodiversity patterns of estuarine benthic communities. A specific field survey allowed us to explain the response of organisms to mixtures of chemicals and the effects of salinity regime and extreme events on the richness and composition of macroinvertebrate assemblages. The patterns obtained provide further evidence that both stress sources are key factors in macroinvertebrate communities' organization, but the type and magnitude of the changes differ. The abundance of opportunistic species increased according to the pollution gradient, while this indicator was less sensitive to salinity descriptors. In contrast, biotic indices responded to the salinity regime but did not show a consistent pattern in response to pollutants. Multivariate analyses reflected both environmental stress gradients. Overall, the results suggested that diversity increased in the habitats where the frequency and duration of extreme drought and flood events were low. Highlights: Natural and anthropogenic stress affects macroinvertebrates differently. Richness and diversity responded to the salinity regime, but not to chemical pollution. Opportunistic species show a correlation to pollution, but not to salinity descriptors. The role of the intensity, frequency and duration of extreme events is highlighted.